Legal Controls for Transfer and Transplantation of Human Organs and Tissues in Sultanate of Oman- Reality and Hope - Mohammed , Lateefah (Journal of Legal Sciences, 2023)
This study ideals with the Omani legal regulations of transferring and transplanting human organs and tissues in light of the Minister of Health decree No. 179 on the year 2018. As the last update, article 27 in 2019 has prohibited conducting such operations unless permission from the Minister of Health is obtained. In the absence of a further law update until the completion of writing the research, we intend to analyze and study some of the current provisions for the transfer and transplantation of human organs and tissues, compared to the legislative trends of some related laws. To achieve this, we divided the study into three sections; the first section introduces the historical development of the legislator criminal policy in regulating the transferring and transplanting from the first enacted law of 1973 until 2022. In addition, we tend to explore the legal justifications that call for the legislator to pass a law on the transfer and transplantation of human organs. The second section addresses the provisions of donating organs and tissues from living people. We focused on the eligibility required for living organ donation and the extent to which it is permissible to obtain blood-producing cells from an underage child. The last section deals with relatives; consent and the permissibility of organ donation after death for those who have completed 15 years of age or are incapable and stipulated provisions for obtaining the organ from those sentenced to death while alive or from unidentified bodies. A law relating to the transfer and transplantation of human organs provides all the provisions for such operations. It stipulates special criminal penalties for violating some judgments.